Perioperative Continuation of Buprenorphine at Low–Moderate Doses Was Associated with Lower Postoperative Pain Scores and Decreased Outpatient Opioid Dispensing Compared with Buprenorphine Discontinuation. Issue 9 (13th March 2020) - Quaye, Aurora; Potter, Kevin; Roth, Sarah; Acampora, Gregory; Mao, Jianren; Zhang, Yi
Abstract: Objective: An increasing number of individuals are prescribed buprenorphine as medication-assisted treatment for opioid use disorder. Our institution developed guidelines for perioperative buprenorphine continuation with an algorithm for dose reduction based upon the surgical procedure and patient's maintenance dose. The objective of this study was to compare the effects of buprenorphine continuation with those of discontinuation on postoperative pain scores and outpatient opioid dispensing. Design: Retrospective observational study. Subjects: Surgical patients on buprenorphine from March 2018 to October 2018. Patients on buprenorphine for chronic pain and those with minor procedures were excluded from analysis. Methods: We compared postoperative outpatient opioid dispensing and postanesthesia care unit (PACU) pain scores in patients where buprenorphine was continued compared with held perioperatively, collecting single surgical subspecialty prescriber data on outpatient full mu-opioid agonist prescriptions dispensed, converted into mean morphine equivalents. Buprenorphine formulations were not included in our morphine milligram equivalents (MME) total. Results: There were 55 patients total (38 cont. vs 17 held). There was no difference in postoperative buprenorphine treatment adherence (91% cont. vs 88% held, P  = 0.324). The number of opioid prescriptions dispensed was significantly higher with buprenorphine discontinuation (53% cont. vs 82% held, P  = 0.011), as was MME dispensed (mean of 229 cont. vs mean of 521 held, P  = 0.033). PACU pain scores were higher with buprenorphine discontinuation (mean 2.9 cont. vs mean 7.6 held, P  < 0.001). Conclusions: There was a significant reduction in opioid prescriptions filled, MME dispensed, and PACU pain scores in patients where buprenorphine was continued vs held perioperatively. We provide evidence to support that buprenorphine can be continued perioperatively and that continuation is associated with decreased postoperative pain and decreased outpatient opioid dispensing. These results contribute to the existing literature supporting the perioperative continuation of buprenorphine.